Positive youth development from a "3Cs" programming perspective: a multi-study investigation in the university. Issue 4 (2nd October 2019) - Kong, Siu-Cheung; Wang, Yi-Qing
ABSTRACT: Background and Context : Positive youth programming development (PYPD) was conceptualized to measure various positive qualities of students in programming education. Objective : This study aimed to develop a valid PYPD instrument in the pilot before exploring students' positive qualities in two follow-up studies. Method : A multi-study design was adopted with questionnaires distributed among university students enrolled in programming courses. In pilot study, the PYPD instrument was developed and validated using confirmatory factor analysis (CFA). Study 1 used independent T-tests to explore potential factors that were predictive of students' PYPD differences. Study 2 conducted paired T-tests to examine students' PYPD improvement. Findings : Results supported validity of the PYPD instrument; provided evidence that intrinsic motivation is particularly crucial for PYPD differences; and showed positive improvement of students' PYPD. Implications : Our findings shed light on existing literature that programming education can play an importantly role if educators want to nurture positive qualities in students.